2011
DOI: 10.1007/s00270-011-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure in Nonvascular Fluoroscopy-Guided Interventional Procedures

Abstract: To establish Diagnostic Reference Levels (DRLs), there is a need to establish a registry of radiation dose data for the most commonly performed procedures. Documentation of interventional procedures by fluoroscopy "grabbing" has the potential to considerably reduce radiation dose applied and should be used instead of radiographic frames whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…Among others, Peruzzo Cornetto et al tabulated data for 23 procedures in an Italian hospital, Compagnone et al published data from a different Italian hospital for nine interventional procedures, Dauer et al published P KA data for 43 interventional fluoroscopy procedures at a single U.S. institution, Bundy et al did the same for 12 procedures at a different U.S. medical center, Erskine et al published P KA data for 32 interventional fluoroscopy procedures in Australia, Étard et al’s report contains data from France for 15 procedures, Pitton et al published data for 17 interventional vascular procedures at a German hospital, Schmitz et al reported data on biliary interventions at 23 different facilities, and Ruiz‐Cruces et al reported data for seven interventional procedures performed at eight hospitals in Spain. Many other published studies were also consulted to estimate one or more of P KA , E , and DC E …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among others, Peruzzo Cornetto et al tabulated data for 23 procedures in an Italian hospital, Compagnone et al published data from a different Italian hospital for nine interventional procedures, Dauer et al published P KA data for 43 interventional fluoroscopy procedures at a single U.S. institution, Bundy et al did the same for 12 procedures at a different U.S. medical center, Erskine et al published P KA data for 32 interventional fluoroscopy procedures in Australia, Étard et al’s report contains data from France for 15 procedures, Pitton et al published data for 17 interventional vascular procedures at a German hospital, Schmitz et al reported data on biliary interventions at 23 different facilities, and Ruiz‐Cruces et al reported data for seven interventional procedures performed at eight hospitals in Spain. Many other published studies were also consulted to estimate one or more of P KA , E , and DC E …”
Section: Resultsmentioning
confidence: 99%
“…There is no consistent method used in the literature for categorizing interventional fluoroscopy procedures. Some of the literature uses very specific categories, based on the specific type and anatomic location of procedures, and sometimes on the indication for the procedure . Other literature uses more general categories .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A registry analysis of 17 centers [8] with 106 data sets described a median DAP of 430 cGy*cm 2 . Kloeckner et al [9] report a median DAP of 3260 cGy*cm 2 . Baumann et al investigated the influence of real time dosimetry on the level of radiation exposure among other things during 9 gastrostomies.…”
Section: Discussionmentioning
confidence: 99%
“…Kloeckner et al [9] report a mean fluoroscopy time of 5.9 minutes. In their article Baumann et al describe how the use of real-time dosimetry [10] allowed an increase of fluoroscopy time from 5.6 to 7.6 minutes with a corresponding reduction of DAP.…”
Section: Discussionmentioning
confidence: 99%